The Influence of Brand Image and Customer Satisfaction Towards Customer Loyalty in Fore Coffee Summarecon Mall Serpong - yehezkiel triputra; ida bagus putu aditya; siti nurfitrana; indra krishnamurti (LIAISON JOURNAL OF BEST, 2023)
Companies must be able to retain customers in a variety of ways, including by emphasizing brand image, which can attract new customers, and customer happiness, which can lead to customer loyalty. Customer loyalty is one of the most significant variables in sustaining a company's growthand expanding its sales. A large number of public figures have opened companies, including restaurants, cafes, and snacks. Numerous entrepreneurs that enter the business field have prominent names to establish a positive brand image with consumers. Vico Lomar, who started a fore coffee business, is one of the businesspeople participating in this industry. This study combines descriptive and quantitative methods. This study was undertaken to determine the association between threevariables: Brand Image, Customer Satisfaction, and Customer Loyalty. This study uses both primary and secondary sources to acquire its data. Survey methods will be used to collect primary data, while secondary data sources, such as books, journals, and articles from prior studies, will be used to obtain secondary data. Customers who bought Fore Coffee via an online application and dined at Fore Coffee in Summarecon Mall Serpong comprised the study population (Gofood, Grabfood and application). If the consumer is pleased with the product, he or she will purchase it again (Repurchase Behavior). This study aims to examine the relationship between Brand Image and Customer Satisfaction and customer loyalty. This study demonstrates that Customer Satisfaction has a greaterimpact on customer loyalty than Brand Image.Keywords: Fore Coffee, Brand Image, Customer Satisfaction, Customer Loyalty